Finite mathematics practical applications - Johnson, David B. (David Bruce) 1949- (Brooks/Cole Pub., 1999)
This text seeks to provide students with an appreciation for and an understanding of finite mathematics and its real-world applications. With in-text calculator instructions, a just-in-time algebra review, and relevant applications, the subject matter should be understandable and accessible.